Porcelain insulation – defining the underlying mechanism of failure - Joni Kluss; Mojtaba Rostaghi Chalaki; Mojtaba Rostaghi Chalaki; Wilburn Whittington; Hongjoo Rhee; Samuel Whittington; Aref Yadollahi (High Voltage, 2019)
Porcelain insulators have a long history and wide application range in power systems, but just like any other insulator, they can fail. A number of pole fires occurred on lines utilising porcelain suspension insulators. In some cases, the insulators appeared to be visually intact with no external signs of degradation or abnormal stress. This prompted a comprehensive assessment to identify the mechanism that leads to the permanent loss of insulating properties while retaining external physical characteristics. A single test is not sufficient to determine the underlying cause of conduction as results may produce contradictory conclusions. Electrical tests were able to identify samples with poor dielectric strength. Nevertheless, these same samples exhibited excellent mechanical properties. Despite successfully passing numerous porosity tests, scanning electron microscopic analysis revealed porosity and multiple microscopic punctures in the porcelain dielectric. Only upon complete dissection of samples, the conduction mechanism was revealed. This article discusses the challenges associated with establishing the root failure mechanism for the investigated porcelain insulators that allows visually sound samples to lose their insulating properties without experiencing catastrophic failure.